Self-reported history of head injury is associated with cognitive impulsivity on a delay discounting task - M. Todd Allen; Alejandro Interian; Vibha Reddy; Kailyn Rodriguez; Catherine E. Myers (PeerJ)
Background Head injuries are a major health care concern that can produce many long lasting cognitive, mental, and physical problems. An emerging literature indicates increased impulsivity in patients with a history of traumatic brain injury (TBI). In a recent study, Veterans with clinically-assessed history of mild TBI had increased cognitive, but not motor, impulsivity. Cognitive impulsivity refers to a preference for smaller immediate rewards (i.e., less willing to wait for larger rewards) while motor impulsivity refers to difficulty inhibiting a motor response. This study extended this work to investigating cognitive and motor impulsivity in a non-clinical sample of putatively healthy undergraduates self-reporting a history of head injury. Methods One hundred and sixteen undergraduates, fifty reporting a history of head injury (HI+) and sixty-six reporting no head injury (HI-), participated in an online study via Qualtrics. They completed a series of demographic questionnaires, the UPPS Impulsive Behavior Scale, a computer-based Go/No-go task to assess motor impulsivity, and a computer-based version of the Monetary Choice Questionnaire (MCQ) to assess cognitive impulsivity. Results HI+ individuals exhibited cognitive impulsivity, measured as a reduced willingness to wait for a larger delayed reward in the MCQ, as compared to HI- individuals. There were no significant differences in performance on the Go/No-go task between the HI+ and HI- groups. Overall, these findings that a self-reported history of head injury in a non-clinical sample are related to cognitive impulsivity, but not motor impulsivity, are consistent with findings from Veterans with clinically-assessed mild TBI. Future work should assess more details on head injuries to further explore how a head injury relates to cognitive impulsivity.